Impact of a treatment escalation/limitation plan on non-beneficial interventions and harms in patients during their last admission before in-hospital death, using the Structured Judgment Review Method. Issue 10 (31st October 2018) - Lightbody, Calvin J; Campbell, Jonathan N; Herbison, G Peter; Osborne, Heather K; Radley, Alice; Taylor, D Robin
Abstract : Objectives: To assess the effect of using a treatment escalation/limitation plan (TELP) on the frequency of harms in 300 patients who died following admission to hospital. Design: A retrospective case note review of 300 unselected, consecutive deaths comprising: (1) patients with a TELP in addition to a do-not-attempt cardiopulmonary resuscitation order (DNACPR); (2) those with DNACPR only; and (3) those with neither. Patient deaths were classified retrospectively as 'expected' or 'unexpected' using the Gold Standard Framework Prognostic Indicator Guidance. Setting: Medical, surgical and intensive care units of a district general hospital. Outcomes: The primary outcome was the between-group difference in rates of harms, non-beneficial interventions (NBIs) and clinical 'problems' identified using the Structured Judgement Review Method. Results: 289 case records were evaluable. 155 had a TELP and DNACPR (54%); 113 had DNACPR only (39%); 21 had neither (7%). 247 deaths (86%) were 'expected'. Among patients with 'expected' deaths and using the TELP/DNACPR as controls (incidence rate ratio (IRR)=1.00), the IRRs were: for harms, 2.99 (DNACPR only) and 4.00 (neither TELP nor DNACPR) (p<0.001 for both); for NBIs, the corresponding IRRs were 2.23 (DNACPR only) and 2.20 (neither) (p<0.001 and p<0.005, respectively); for 'problems', 2.30 (DNACPR only) and 2.76 (neither) (p<0.001 for both). The rates of harms, NBIs and 'problems' were significantly lower in the group with a TELP/DNACPR compared with 'DNACPR only' and 'neither': harms (per 1000 bed days) 17.1, 76.9 (p<0.001) and 197.8 (p<0.001) respectively; NBIs: 27.4, 92.1 (p<0.001) and 172.4 (p<0.001); and 'problems': 42.3, 146.2 (p<0.01) and 333.3 (p<0.001). Conclusions: The use of a TELP was associated with a significant reduction in harms, NBIs and 'problems' in patients admitted acutely and who subsequently died, especially if they were likely to be in the last year of life.